Sąsiedzkie prawo pierwokupu a struktura gruntowa polskich gospo-darstw rolnych – panaceum czy pandemonium? - Blajer, Paweł (Wydawnictwo Naukowe UAM, 2015)
The article tackles the issue of the neighbour’s right of first refusal introduced to the legislation by the Act of 5 August 2015 on the Shaping of the Agricultural Regime. The aim of the deliberations was to confront this new, under Polish law, institution with solu-tions that have been for long operational in Italy and Spain. The research also took into account some premises of the regulation, in particular the manner in which it will be im-plemented. The results of the analysis are expected to answer the question formulated in the title of the article, whether the neighbour’s right of first refusal is an effective tool for the shaping of a proper agrarian structure of Polish agricultural holdings, or, whether to the contrary, when shaped as provided in the Act, this new solution will put the trading in agri-cultural land on hold. In the concluding remarks critical opinions of the new regulation are formulated with a suggestion that legislative work be undertaken to amend the provisions of the regulation having regard for the results of a comparative study.

L’oggetto delle considerazioni è il diritto di prelazione del confinante introdotto nella legge del 5 agosto 2015 sulla configurazione dell’ordinamento agrario. L’obiettivo dello studio è di confrontare l’istituto di prelazione del confinante, nuovo nel sistema polacco di diritto agrario, con le soluzioni da anni funzionanti in Italia e Spagna. Le ulteriori consi-derazioni terranno conto delle premesse oggettive e soggettive del diritto in oggetto e – in particolare – della modalità di attuazione. I risultati dell’analisi dovranno permettere di rispondere alla domanda formulata nel titolo, vale a dire se il diritto di prelazione del confinante costituisca effettivamente uno strumento per la configurazione di una corretta struttura fondiaria delle aziende agricole polacche oppure se, al contrario, l’istituto in esame, nella forma prevista dalla legge, possa portare ad una sospensione nella compravendita dei fondi agricoli. Nella parte conclusiva l’autore formula una valutazione critica dell’istituto giuridico analizzato. La sua entrata in vigore rischia addirittura di portare ad una paralisi nella compravendita dei fondi agricoli. Per cui pare indispensabile intraprendere lavori legislativi volti a cambiare le disposizioni relative a questo istituto, dando più rilievo ai risultati della ricerca comparata. L’analisi giuridica comparata fornisce infatti tante indicazioni specifiche relative ad una potenziale forma di “prelazione del confinante” di stampo polacco.
Neighbour’s right of first refusal and the land structure of Polish ag-ricultural holdings – panaceum or pandemonium?
Il diritto di prelazione del confinante e la struttura fondiaria delle aziende agricole polacche – panaceum o pandemonium?